Asthma in the elderly: a different disease?. Issue 1 (March 2016) - Battaglia, Salvatore; Benfante, Alida; Spatafora, Mario; Scichilone, Nicola
Key points: Asthma in the elderly can be difficult to identify due to modifications of its clinical features and functional characteristics. Several comorbidities are associated with asthma in the elderly, and this association differs from that observed in younger patients. In clinical practice, physicians should treat comorbidities that are correlated with asthma ( i.e. rhinitis or gastro-oesophageal reflux), assess comorbidities that may influence asthma outcomes ( i.e. depression or cognitive impairment) and try to prevent comorbidities related to 'drug-associated side-effects ( i.e. cataracts, arrhythmias or osteoporosis). "Geriatric asthma" should be the preferred term because it implies the comprehensive and multidimensional approach to the disease in the older populations, whereas "asthma in the elderly" is only descriptive of the occurrence of the disease in this age range. Educational aims: To present critical issues in performing differential diagnosis of asthma in the elderly. To offer the instrument to implement the management of asthma in the most advanced ages. : Asthma is a chronic airway disease that affects all ages, but does this definition also include the elderly? Traditionally, asthma has been considered a disease of younger age, but epidemiological studies and clinical experience support the concept that asthma is as prevalent in older age as it is in the young. With the ever-increasing elderly population worldwide, the detection and proper management of the disease in old age may have a great impact from the public health perspective. Whether asthma in the elderly maintains the same characteristics as in young populations is an interesting matter. The diagnostic process in older individuals with suspected asthma follows the same steps, namely a detailed history supported by clinical examination and laboratory investigations; however, it should be recognised that elderly patients may partially lose reversibility of airway obstruction. The correct interpretation of spirometric curves in the elderly should take into account the physiological changes in the respiratory system. Several factors contribute to delaying the diagnosis of asthma in the elderly, including the age-related impairment in perception of breathlessness. The management of asthma in advanced age is complicated by the comorbidities and polypharmacotherapy, which advocate for a comprehensive approach with a multidimensional assessment. It should be emphasised that older age frequently represents an exclusion criterion for eligibility in clinical trials, and current asthma medications have rarely been tested in elderly asthmatics. Ageing is associated with pharmacokinetic changes of the medications. As a consequence, absorption, distribution, metabolism and excretion of antiasthmatic medications can be variably affected. Similarly, drug-to-drug interactions may reduce the effectiveness of inhaled medications and increase the risk of side-effects. For this reason, we propose the term "geriatric asthma" be preferred to the more generic "asthma in the elderly". Asthma in the elderly: is it time think differently? http://ow.ly/Y71zN